Pharmacokinetic interaction of drugs, the metabolisable cytochrome P450 isoenzyme CYP2C9 - O. G. Gribakina; G. B. Kolyvanov; A. A. Litvin; A. O. Viglinskaya; V. P. Zherdev (LLC "Publisher OKI", 2020)
The role of cytochrome P450 isoforms CYP2C9 and in the metabolism of losartan described. Losartan pharmacokinetics data in humans and laboratory animals are presented. Examples of drug-drug interactions of substrate marker losartan of CYP2C9 of with different drugs are given. The results of studies of the effects of afobazole, an inducer (rifampicin) and inhibitors (fluconazole) in effective doses on the pharmacokinetics of losartan.